2021
DOI: 10.3389/fpsyg.2021.682153
|View full text |Cite
|
Sign up to set email alerts
|

Role of Personality and Positive and Negative Affects in Coping Strategies of Nurses: A Cross-Sectional Study

Abstract: Nurses are exposed to many highly stressful events. Individual variables, such as personality and affective state, have been related to vulnerability to maladaptive coping. Therefore, the objectives of this study were to analyze the relationships between the personality, positive and negative affects, and coping strategies of nurses and to establish the mediating role of affective state in the relationship between personality and coping. The sample was made up of 1,268 Spanish nurses aged 22–63 years who compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…Aside from perspective-taking, identifying the positive assets was also an engagement strategy in intensive care nurses, which was paid less attention in previous study. The factor behind this may lie in the non-confrontational personality traits in Chinese culture, which brought about positive re ection when dealing with ethical con ict [41]. We found that some of the intensive care nurses pondered the experience of ethical con ict when undergoing situational triggers.…”
Section: Discussionmentioning
confidence: 83%
“…Aside from perspective-taking, identifying the positive assets was also an engagement strategy in intensive care nurses, which was paid less attention in previous study. The factor behind this may lie in the non-confrontational personality traits in Chinese culture, which brought about positive re ection when dealing with ethical con ict [41]. We found that some of the intensive care nurses pondered the experience of ethical con ict when undergoing situational triggers.…”
Section: Discussionmentioning
confidence: 83%
“…Aside from perspective-taking, identifying the positive assets was also an engagement strategy in intensive care nurses, which was paid less attention in previous studies [ 10 13 ]. The factor behind this may lie in the non-confrontational personality traits in Chinese culture, which brought about positive reflection when dealing with ethical conflict [ 41 ]. We found that some of the intensive care nurses pondered the experience of ethical conflict when undergoing situational triggers.…”
Section: Discussionmentioning
confidence: 99%
“…In another study conducted by Martos Martínez et al among Spanish nurses, it was shown that effective coping with stress is affected by the subjective properties of an individual. Some individual variables, such as personality and an affective state can be regarded as stress moderators [ 13 ]. Psychological stress has been demonstrated to be associated with somatic health disorders [ 4 ].…”
Section: Introductionmentioning
confidence: 99%